SPEECHES AFTER RECEIVING THE SERIAL NUMBER IN 2023 - aunike N peranginanginN; Sahlan Tampubolon; Carolina Pakpahan (English Language Teaching Prima Journal (ELT), 2024)
This thesis examines the modalities used in the speeches of the three presidential candidates after receiving serial numbers in 2023. By analyzing the clauses they convey, this thesis aims to understand the ideologies of the three presidential candidates, as well as how they make their speeches. delivered to convince the public. The research method used is descriptive qualitative using documentation as a data collection method. The analysis was carried out by referring to Halliday's (2014) SFL theory. The focus of this research is on modality sentences in the speeches of the three presidential candidates. Researchers found 38 sentences that used modalities in the speeches of the three presidential candidates after receiving serial numbers in 2023. The modalities that the three presidential candidates often used in their speeches were obligation modulation, desire and probability modulation, where the three presidential candidates stated something that was considered mandatory and could not be done. bargained for and expressed his desire and confidence in holding the election. The dominant use of modulation in the speeches of the three presidential candidates, with the aim of inviting the audience to take certain actions together and influencing the audience in choosing a presidential candidate who can defend and advance the Indonesian state. It is hoped that the results of this research will help the public to see the strategies of the three presidential candidates in influencing the public through their speeches so that the public can choose them.